Strategy for Developing a Halal - Green Cosmetics Msmes Business Model: a Case Study of CV. Berkah Bersama Tanzif - Agam Gumawang; Ira Setyaningsih; Dwi Agustina Kurniawati (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
The rapid growth of the halal cosmetics industry, accompanied by increasing consumer awareness of sustainability and ethical production, has created new strategic challenges for micro, small, and medium enterprises (MSMEs) in Indonesia. Many halal cosmetic MSMEs face limitations in structured business planning, digital capability, and innovation integration, which may hinder their competitiveness in an increasingly dynamic market. This study aims to formulate a comprehensive halal green business model for CV. Berkah Bersama Tanzif as a strategic response to the evolving halal cosmetics ecosystem. Employing a descriptive qualitative research design, data were collected through in-depth interviews, field observations, and documentation analysis. The analytical framework integrated Business Model Canvas (BMC) mapping with Internal External Factor Analysis, SWOT analysis, and the Quantitative Strategic Planning Matrix (QSPM). The findings indicate that the company has successfully integrated halal assurance principles with sustainability-oriented practices across the nine BMC components, which were refined into a Halal Green Business Model Canvas (HGBMC). Key internal strengths include strong halal values, leadership commitment, complete certification, continuous product innovation, and digital marketing utilization, while external opportunities arise from regulatory support, growing demand for halal-natural cosmetics, and global market expansion. QSPM results identify global halal green market expansion as the most attractive strategic priority, followed by product differentiation and supply chain strengthening. This study contributes to the development of halal-based business model theory by demonstrating how halal governance and environmental sustainability can be systematically integrated to enhance MSME competitiveness in the cosmetic sector.